Efek Latihan Aerobik Terhadap Irisin Dalam Mencegah Obesitas - Naufal Firdaus; Sugiharto Sugiharto; Desiana Merawati (Program Studi Ilmu Keolahragaan, 2023)
Aerobic exercise is rated as the most effective strategy for treating obesity. Aerobic exercise induces irisin to stimulate tissue browning. The important role of irisin in the regulation of metabolism and reduction of body fat is that it can increase energy expenditure. The method of this article is to look at several journal articles that compare one journal to another. In practice, the results of the analysis of research journals are combined based on their respective similarities and differences to produce new conclusions. The results Aerobic exercise induces the release of irisin via peroxisome proliferation activated receptor-γ (PPAR-γ) and PGC-1α. Exercise that is performed at intervals increases PGC-1α activation, especially in the heart and skeletal muscles and improves various metabolic parameters such as insulin sensitivity and signaling, promotes AMPK activation, PGC1α phosphorylation and FNDC5 production, followed by cleavage of FNDC5 to produce irisin which will be released into the blood circulation. . The release of irisin into the blood circulation activates the AMPK pathway by reducing intracellular ATP or by increasing the intracellular calcium concentration in muscle cells, causing increased glucose and lipid uptake and increased fat metabolism. Aerobic exercise can increase irisin in an obese person which has an effect on energy expenditure so that fat in the body is reduced and subsequently results in weight loss.